PENGARUH DISIPLIN DAN PELATIHAN TERHADAP KINERJA PEGAWAI PADA SUKU DINAS PENANGGULANGAN KEBAKARAN DAN PENYELAMATAN KECAMATAN KEBAYORAN JAKARTA SELATAN - Indah Savitri, Shela; Fauzi Imansyah, Reza (Accounting UNIPA - Jurnal Akuntansi, 2024)
The aim of this research is to determine the effect of discipline and training on employee performance at the Kebayoran District Fire and Rescue Service, South Jakarta. This type of research is quantitative with an associative method. The population in this was 112 employees of the South Jakarta Kebayoran District Fire Handling and Rescue Department, while the sample used was 87 respondents using a slovin sampling technique. The data collection technique is by means of a questionnaire. Data analysis techniques using simple linear regression and multiple regression tests. The results of the research show that there is a positive and significant influence of discipline on employee performance at the Fire Handling and Rescue Sub-Department, Kebayoran District, South Jakarta. This can be proven from the simple linear regression equation Y = 12.834 + 0.656X1. The correlation value is 0.664 (strong). The coefficient of determination value is 44.1%, and the value of tcount > ttable (8.189 > 1.988) is significant (0.000 < 0.05). There is a positive and significant influence of training on employee performance at the South Jakarta Kebayoran District Fire Handling and Rescue Service. This can be proven from the simple linear regression equation Y = 11.998 + 0.667X2. The correlation value is 0.630 (strong). The coefficient of determination value is 39.7%, and the value of tcount > ttable (7.482 > 1.988) is significant (0.000 < 0.05). Simultaneously, there is a positive and significant influence of discipline and training on employee performance at the Kebayoran Jakarta District Fire and Rescue Service. This can be proven from the multiple linear regression equation Y = 8.258 + 0.432X1 + 0.334X2. The correlation value is 0.699 (strong). The coefficient of determination value is 48.9%, and the value of Fcount > Ftable (40.190 > 3.11) with a significant level (0.000 < 0.05).